Effects of fermented feed of Pennisetum giganteum on growth performance, oxidative stress, immunity and gastrointestinal microflora of Boer goats under thermal stress - Qiu, Yuyang; Zhao, Hui; He, Xiaoyu; Zhu, Furong; Zhang, Fengli; Liu, Bin; Liu, Qinghua (Frontiers in Microbiology, 2023)
Introduction This study was conducted to evaluate the effects of fermented feed of Pennisetum giganteum (P. giganteum) on growth performance, oxidative stress, immunity and gastrointestinal microflora of Boer goats under thermal stress. Methods The study was conducted during 45 days using twenty 2 months Boer goats. The goats were randomly allocated into two groups: NPG (n = 10; normal P. giganteum) and FPG (n = 10; fermented feed of P. giganteum), and the ratio of concentrates to roughage was 3:2. Both groups of animals were kept in sheds and exposed to summer thermal stress from 10:00 h to 18:00 h (temperature and humidity index, THI > 78). At the end of the study, the animals were slaughtered and assessed for various characteristics. Results The findings from the study revealed that FPG-feeding significantly increased (p < 0.05) average daily gain (ADG, 48.18 g) and carcass weight (4.38 kg), while decreased (p < 0.01) average daily feed intake (ADFI, 0.74 kg/d; p < 0.01) and the feed:gain (F/G, 15.36) ratio. The CAT, GSH-Px activities and GSH in serum, liver and spleen, and the levels of IgA, IgG, IgM, IL-2, IL-4 and IL-1β in serum of FPG-fed goats were significantly higher (p < 0.05) than those of NPG-feeding goats. Further, we found that FPG feed is rich in nutrients with Lactobacillus (65.83%) and Weissella (17.80%). Results for gastrointestinal microbiota composition showed that FPG-feeding significantly enhanced the abundance of Lactobacillus and unidentified Clostridiales, and reduced Anaerovibrio and Methanobrevibacter. Meanwhile, Spearman’s correlation analysis showed that these microbiotas were closely related to the improvement of oxidative stress and immune indexes of goats. Discussion These results demonstrated that FPG-feeding not only reduces oxidative stress and improves ROS clearance to enhance antioxidant defense system, but also improves gastrointestinal microbiota to enhance immune function by overcoming the adverse effects of heat stress, and further improve growth performance of goats.